Muscle transcriptome analysis provides new insights into the growth gap between fast- and slow-growing Sinocyclocheilus grahami - Yin, Yanhui; Zhang, Yuanwei; Hua, Zexiang; Wu, Anli; Pan, Xiaofu; Yang, Junxing; Wang, Xiaoai (Frontiers in Genetics, 2023)
Sinocyclocheilus grahami is an economically valuable and famous fish in Yunnan Province, China. However, given its slow growth (40 g/2 years) and large growth differences among individuals, its growth performance needs to be improved for sustainable future use, in which molecular breeding technology can play an important role. Therefore, in the current study, we conducted muscle transcriptomic analysis to investigate the growth gaps among individuals and the mechanism underlying growth in S. grahami. In total, 1 647 differentially expressed genes (DEGs) were obtained in 14 fast-and 14 slow-growth individuals, including 947 up-regulated and 700 down-regulated DEGs in fast-growth group. Most DEGs were significantly enriched in 2 ECM-receptor interaction, starch and sucrose metabolism, glycolysis/gluconeogenesis, pyruvate metabolism, amino acids biosynthesis and metabolism, peroxisome, and PPAR signaling pathway. Some genes related to glycogen degradation, glucose transport, and glycolysis (e.g., adipoq, prkag1, slc2a1, agl, pygm, pgm1, pfkm, gapdh, aldoa, pgk1, pgam2, bpgm, and eno3) were up-regulated, while some genes related to fatty acid degradation and transport (e.g., acox1, acaa1, fabp1b.1, slc27a1, and slc27a2) and amino acid metabolism (e.g., agxt, shmt1, glula, and cth) were down-regulated in the fast-growth group. Weighted gene co-expression network analysis identified col1a1, col1a2, col5a1, col6a2, col10a1, col26a1, bglap, and krt15 as crucial genes for S. grahami growth. Several genes related to bone and muscle growth (e.g., bmp2, bmp3, tgfb1, tgfb2, gdf10 and myog) were also up-regulated in the fast-growth group. These results suggest that fast-growth fish may uptake adequate energy (e.g., glucose, fatty acid, and amino acids) from fodder, with excess energy substances used to synthesize collagen to accelerate bone and muscle growth after normal life activities are maintained. Therefore, energy uptake may be the root cause, while collagen synthesis may be the direct reason for the growth gap between fast-and slow-growth fish. Hence, improving food intake and collagen synthesis may be crucial for accelerating S. grahami growth, as are genes related to appetite, food intake (e.g., adipoq), and collagen synthesis (e.g., col1a1, col1a2, col5a1, col6a2, col10a1, col26a1). However, further research is required to fully understand and confirm these associations.